Pengaruh Kualitas Produk, Harga dan Saluran Distribusi Terhadap Keputusan Pembelian Beras (Studi Kasus Konsumen Kilang Padi UD Makmur Jaya di Desa Makmur Kecamatan Teluk Mengkudu Kabupaten Serdang Bedagai) - Yogi, Sulastri; Fikri, Muhammad Hilman (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of product quality, price and distribution channels on rice purchasing decisions (Case Study of UD Makmur Jaya Rice Mill Consumers in Makmur Village, Teluk Mengkudu District, Serdang Bedagai Regency). The sample for this research was 95 consumers. The results of this research are that the variables of product quality, price and distribution channels simultaneously have a positive and significant effect on rice purchasing decisions, with a coefficient of determination value of 0.872